Effect of the addition of Sc element on the microstructure and properties of Al80Li5Mg5Zn5Cu5 high-entropy alloy - Zhiqiang Li; Weili Wang; Xuanqi Chen; Bo Peng; Hui Xing; Jieren Yang (Journal of Materials Research and Technology)
This study added a trace amount of Sc element (1 at%) to the Al-Li-Mg-Zn-Cu lightweight high-entropy alloy (LHEA) system. It was found that after minor alloying with Sc, a new strengthening precipitate phase (Al₃Sc) appeared in the alloy, which effectively inhibited grain growth, reducing the average grain size of Al₈₀Li₅Mg₅ Zn₅Cu₅ from 548.2 μm to 28.4 μm, significantly refining the grain structure. The addition of the Sc element not only improves the mechanical properties of the high-entropy alloy, but it is also found that Sc element is able to provide the alloy with an additional layer of passivation film during the corrosion process, which exhibits more excellent corrosion resistance. To achieve better performance of the Al₈₀Li₅Mg₅Zn₅Cu₄Sc₁ high-entropy alloy, the distribution and size of the precipitate phase and matrix phase were regulated through heat treatment. It was found that after holding at 400 °C for 1 h, the room temperature tensile and compressive strengths of the Sc-containing HEA increased by 68.8% and 63.4%, respectively, compared to the as-cast structure. Furthermore, the room temperature ductility of the Sc-containing high-entropy alloy improved from 0.5% in the as-cast state to 6.8% after holding at 400 °C for 4 h.